Analisa Dan Visualisasi Data Penjualan Menggunakan Exploratory Data Analysis Pada PT. Telkominfra - Aditya Wibowo; Khatin Faisah; Yudo Devianto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Telkominfra's business is growing with large projects with a high level of complexity making it difficult to process data. Data processing process starting from exporting, filtering data, analyzing data, and making data visualization is still done using excel files, this takes quite a long time so that the decision-making process carried out by management becomes less than optimal . The purpose of this research is expected to be able to provide information and knowledge related to the users in real time so that it can speed up the decision-making process. Therefore, it is necessary to analyze data using the Exploratory Data Analysis (EDA) method, EDA is carried out starting from understanding the business object where revenue/sales is one of the metrics used to see the company's performance profile. The results of this study show that the comparison of monthly revenue, the comparison of revenue for each product and the composition of the lowest revenue realization so that it can be evaluated by management, and the results of the EDA will be displayed in a data visualization application.